Dynamics of the Galaxy's Satellites - Binney, J (2000)
The Milky Way's satellites provide unique information about the density of the Galactic halo at large radii. The inclusion of even a few rather inaccurate proper motions resolves an ambiguity in older mass estimates in favour of higher values. Many of the satellites are concentrated into streams. The dynamics of the Magellanic Stream provided an early indication that the halo reaches out to beyond 100 kpc. Tidal forces between the Clouds are currently disturbing the Clouds' internal dynamics. One would expect this damage to worsen rapidly as the tidal field of the MW excites the eccentricity of the Clouds' mutual orbit. This process, which has yet to be completely modelled, is important for understanding the degree of self-lensing in searches for gravitational lensing events. The Sagittarius Dwarf galaxy very likely contributes significantly to the Galactic warp. The direction of the warp's line of nodes is incorrectly predicted by the simplest models of the Dwarf's orbit. More sophisticated models, in which a complex distribution of stripped dark matter is predicted, may be more successful.